THE DEVELOPMENT OF AUTOMATION MANAGEMENT TOOLS BY THE DIVISIONS OF TACTICAL MISSILE DEFENSE - O. V. Voronin; S. V. Potetenko; S. V. Kruglikov (Informatika)
The article summarizes the basic directions of automation for planning and management of combat by the divisions of tactical missile defense. The article focuses on the problem of the automated choice of rational option for combat order and fire control carried out by the divisions of tactical missile defense during operation.